Variation of insulin‐related peptides accompanying the differentiation of Aphis gossypii biotypes and their expression profiles - Weili Jiang; Muhammad Nasir; Chenchen Zhao (Ecology and Evolution)
Abstract Insulin signaling plays a critical role in regulating various aspects of insect biology, including development, reproduction, and the formation of wing polyphenism. This leads to differentiation among insect populations at different levels. The insulin family exhibits functional variation, resulting in diverse functional pathways. Aphis gossypii Glover, commonly known as the cotton‐melon aphid, is a highly adaptable aphid species that has evolved into multiple biotypes. To understand the genetic structure of the insulin family and its evolutionary diversification and expression patterns in A. gossypii, we conducted studies using genome annotation files and RNA‐sequencing data. Consequently, we identified 11 insulin receptor protein (IRP) genes in the genomes of the examined biotypes. Among these, eight AgosIRPs were dispersed across the X chromosome, while two were found in tandem on the A1 chromosome. Notably, AgosIRP2 exhibited alternative splicing, resulting in the formation of two isoforms. The AgosIRP genes displayed a high degree of conservation between Hap1 and Hap3, although some variations were observed between their genomes. For instance, a transposon was present in the coding regions of AgosIRP3 and AgosIRP9 in the Hap3 genome but not in the Hap1 genome. RNA‐sequencing data revealed that four AgosIRPs were expressed ubiquitously across different morphs of A. gossypii, while others showed specific expression patterns in adult gynopara and adult males. Furthermore, the expression levels of most AgosIRPs decreased upon treatment with the pesticide acetamiprid. These findings demonstrate the evolutionary diversification of AgosIRPs between the genomes of the two biotypes and provide insights into their expression profiles across different morphs, developmental stages, and biotypes. Overall, this study contributes valuable information for investigating aphid genome evolution and the functions of insulin receptor proteins.